The Effect of Academic Stress, Burnout, and Class Engagement, on Cyberloafing Behavior in UNTAR Students - Yoshua Zakharia; Sawidji Widoatmodjo (Asian Journal of Social and Humanities, 2023)
Nowadays, human life cannot be separated from technology, especially the internet. The internet helps human activities, so the internet is needed, but with the presence of the internet, humans abuse the internet provided. This phenomenon is known as cyberloafing. Cyberloafing is a form of internet abuse behavior during working hours. Cyberloafing behavior itself is influenced by several variables. The variables examined in this research that influence cyberloafing are academic stress, class engagement, and burnout. This research was conducted with the aim of finding out whether the variables of academic stress, class engagement, and burnout influence a person's cyberloafing behavior. In the process of collecting research data using the Simple Random Sampling (SRS) technique by submitting questionnaires online via WhatsApp, Line and Discord with Google Form. The sample chosen was students studying at Tarumanagara University, with 371 participants studying at Tarumanagara University. The results of this research show that the class engagement and academic stress variables have a positive and significant effect, but the burnout variable has a positive and insignificant effect on cyberloafing behavior. So from this research it can be concluded that academic stress and class engagement variables influence students to carry out cyberloafing